ANALISIS KUALITAS PEGAWAI FRONT OFFICE DALAM PELAYANAN TERPADU SATU PINTU (PTSP) DI KANTOR KEMENTERIAN AGAMA PROVINSI MALUKU - Ike Rahmatia Rahanyamtel; Z. A. Rengifurwarin; Ivonny Rahanra (UNIVED PRESS, Universitas Dehasen Bengkulu, 2023)
This research is descriptive qualitative research. Aims to analyze and explain the description of the Quality Analysis of Front Office Employees in PTSP at the Promal Ministry of Religion Office. The informants of this research amounted to 12 people. The data needed in this study were collected through observation, interview, and documentation techniques. The data was successfully collected, processed and analyzed with the help of descriptive qualitative analysis techniques. The results of this study indicate that the quality of Service by Front Office Employees at the PTSP Unit of the Ministry of Religion Promal is quite good, but not yet optimal as a whole. This is influenced by supporting factors, such as: a) factors of work systems and procedures, b) factors of ability, attitudes and work behavior of employees, and c) technological factors, infrastructure facilities. While the obstacles are, a) employee cooperation factors, and b) employee work motivation factors. The implication of this research, if you want to improve the quality of public services by front office employees at the PTSP of the Promal Ministry of Religion Office, then the things that need to be developed are work systems and procedures, ability, attitudes and work behavior, employee cooperation, as well as improving cooperation, and employee work motivation.